Sistem Penentuan Penambahan Koleksi Buku di Perpustakaan Menggunakan Metode K-Means Clustering - Asminah Asminah (Journal of Information System Research (JOSH), 2022)
In the library of the Pagar Alam Institute of Technology, the process of determining the addition of a book collection is still done manually, namely by taking notes to find out what book data are often borrowed by students, so it takes a long time to find the data archive of book borrowers, to determine the addition of books can be done. seen from the data archive of student book borrowing, because book lending is still done by recording so it is still difficult for officers to find out what books are often borrowed by students. The purpose of this study is to build a system for determining the addition of books in the library of the Pagar Alam Institute of Technology with the K-Means Clustering method which produces 3 clusters, namely cluster 0 which means high, cluster 1 which means medium and cluster 2 which means low. From this study, information was obtained that there were 563 data in cluster 0 with high information, 357 data in cluster 1 with moderate information, and in cluster 2, 290 data with low information with centeroid values ​​for the number of books, namely 1.396, 1.401 and 1.421, centeroid values ​​in information 1,620, 1,627 and 1,621 and the centeroid value on the number of borrowers is 6,362, 10,429 and 2,617. The test method uses Black Box Testing in the form of alpha testing which is tested by experts in the field while database testing obtains an average value of 4, interface testing 4.07, functionality testing 3.93 and algorithm testing with an average of 4 so as to obtain an average a total of 4 and get 80% eligibility results. The results obtained from the research are the System for Determining the Addition of Book Collections in the Library of the Pagar Alam Institute of Technology using the K-Means Clustering Method.